Mitochondrial humanin peptide acts as a cytoprotective factor in granulosa cell survival - Marvaldi, Carolina (2021)
Humanin (HN) is a short peptide involved in many biological processes such as apoptosis, cell survival, inflammatory response, and reaction to stressors like oxidative stress, between others. In the ovary, a correct balance between pro- and anti-apoptotic factors is crucial for folliculogenesis. In the follicular atresia, survival or death of granulosa cells is a critical process. The goal of this study was to evaluate the action of HN on granulosa cell fate. To explore endogenous HN function in the ovary, we used a recombinant baculovirus (BV) encoding a short-hairpin RNA targeted to silence HN (shHN). HN downregulation modified ovarian histoarchitecture and increased apoptosis of granulosa cells. HN was also detected in a granulosa tumor cell line (KGN). Transduction of KGN cells with BV-shHN resulted in HN downregulation and increased apoptosis. On the other hand, treatment of KGN cells with exogenous HN increased cell viability and decreased apoptosis. In summary, these findings indicate that HN is a cytoprotective factor in granulosa cells of antral follicles, suggesting that this peptide would be involved in the regulation of folliculogenesis. Also, this peptide is a cytoprotective factor in KGN cells, and therefore, it could be involved in granulosa tumor cell behavior.